USING SINGLE VALUED NEUTROSOPHIC SET TO SELECT TOURISM DEVELOPMENT STRATEGIES IN EASTERN SERBIA - Urošević, Snežana; Stanujkić, Dragiša; Karabašević, Darjan; Brzaković, Pavle (Economics of Agriculture, 2018)
Natural beauties of Eastern Serbia combined with the culture, traditions, food specialties and music, can become a recognizable tourism brand, which could improve the image of this part of Serbia, and that is the reason why Eastern Serbia has been recently discovering its potential for tourism development. The aim of this paper is to analyze the current and potential elements for tourism development of Eastern Serbias products. Based on the relevant literature and factual situation on the feld, the goal is to rank strategies for tourism development on the territory of Eastern Serbia in order to enable better positioning of tourism in Eastern Serbia on the Serbian tourist map. In order to rank tourism development strategies we have used neutrosophic sets. The justification and usability of the proposed approach for the selection of tourism development strategy is demonstrated in the implemented numerical example.